Equipping Coiled-Coil Peptide Dimers With Furan Warheads Reveals Novel Cross-Link Partners - Miret-Casals, Laia; Van De Putte, Sander; Aerssens, Dorien; Diharce, Julien; Bonnet, Pascal; Madder, Annemieke (Frontiers in Chemistry, 2022)
Using a coiled-coil peptide dimer as a model system to explore furan reactivity, we describe novel cross-link partners of furan warheads for site-specific cross-linking. We demonstrate that replacement of weak interhelical ionic contacts with a furan moiety and its potential cross-link partner, affords covalently connected coiled-coil motifs upon furan activation. We describe for the first time reaction of the activated furan warhead with cysteine and tyrosine, besides the previously reported lysine, thus enhancing the versatility of the furan cross-link methodology by the possibility to target different amino acids. The present in vitro validation of ‘furan-armed’ α-helices provides further ground for exploiting furan-technology in the development of furan-modified ligands/proteins to target proteins in a covalent way through various amino acid side chains.